Ihyā' Al-Qur'an in the Family Dimension: Grounding the Qur'an in the Domestic Space - Arya Dekhan; Sohrah; Muhsin Mahfudz (SETYAKI : Jurnal Studi Keagamaan Islam, 2026)
Contemporary engagement with the Qur’an tends to be confined to formal spaces such as mosques and Islamic boarding schools, while its actualization within the domestic family sphere has eroded. This study aims to explain the concept of ihyā’ al-Qur’an from a family perspective, together with its implementation and the dynamics within the family dimension. Methodologically, this is a conceptual library research employing a descriptive-analytical approach, with the living Qur’an paradigm serving as a theoretical framework for reading literature on Qur’anic family education rather than as an empirical field study. The findings indicate that ihyā’ al-Qur’an within the family encompasses three interrelated dimensions: learning, internalization through tadabbur and muhāsabah, and the practice of Qur’anic values in daily interaction. Its dynamics include strengthening family resilience, Qur’anic education as a management system, and the role of the Qur’an in managing conflict. The study contributes a theoretical-practical model of the Qur’anic family that can serve as a reference for grounding the Qur’an amid the challenges of modernity